REPRESENTATION OF THE NEW REGIME TRANSITION TOWARDS THE REFORMATION ERA IN THE TEMBOK PAK RAMBO SHORT STORY BY TAUFIK IKHRAM JAMIL: INTERTEXTUALITY STUDY - Ni Luh Ayu Sukmawati (Lakon : Jurnal Kajian Sastra dan Budaya, 2020)
The transition era between the New Order Era to the Reformation Era in Indonesia in 1998 became one of the popular themes for Indonesian writers. One of the works entitled Tembok Pak Rambo inserted elements of historical facts that occurred in Indonesia. The representation of the obscurity of the new order in this short story cannot be read only with heuristic readings, therefore a theory is needed to explore more profound the significance of the story. This paper utilizes the intertextuality approach in dismantling the veiled meanings in the story. The results showed that the short story represents two Indonesian leaders in the era of the new order transition to the reform era. This representation appears when aligned with a book called The Long Way of Indonesia Towards Democracy written by B. J. Habibie. Moreover, the short story titled Tembok Pak Rambo is not just about the hegemony between the ruler to his subordinates, but how the Indonesian writers were trying to criticism on the government and the historical facts that happened in 1998.